Energy analysis of a reversed circular flow jet impingement (RCFJI) on a bifacial PVT collector - Muhammad Amir Aziat Ishak,; Adnan Ibrahim,; Mohd Faizal Fauzan,; Ahmad Fazlizan,; Ewe, Win Eng (Penerbit Universiti Kebangsaan Malaysia, 2024)
Although photovoltaic thermal (PVT) offers ascertain of benefits, it also has its own limitations. The efficiency of PVT is diminished due to heat gain experienced by its photovoltaic module when subjected to solar radiation. Jet impingement has been recognised as a highly successful technique for the purpose of cooling solar modules, particularly in the context of bifacial module applications. An energy analysis of a reversed circular flow jet impingement on a bifacial PVT collector was perform through an indoor experiment utilizing a solar simulator. The jet plate outlet was varied into four different configurations: one hole (1h), three holes (3h), four holes (4h) and five holes (5h) to identify the jet plate outlet configuration that contributes to the best energy efficiency. The experiment was carried out using a constant solar irradiance of 900 W/m2 and mass flow rate between 0.01 kg/s to 0.14 kg/s. The study’s findings indicate that configuration 1h exhibited the best photovoltaic efficiency of 11.09%. Additionally, the highest thermal efficiency recorded was 63.2%. In summary, it can be concluded that configuration 1h exhibits an overall photovoltaic thermal efficiency of 74.28% when subjected to a mass flow rate of 0.14 kg/s. This configuration outperforms other jet plate outlet configuration in terms of energy performance.